Review paperSelected questionnaire methods studying the quality of life - Kłak, Anna; Mińko, Magdalena; Siwczyńska, Dorota; Samoliński, Bolesław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
The scientific literature is full of numerous reports dealing with the quality of life of patients suffering from different diseases. The aim of the study is to present a set of questionnaires, which are used to study the quality of the patient’s life, the questionnaires, which are the most popular in Poland and all over the world as well as those which concern the children’s allergy. Increasingly, the research deals with the objective and subjective feelings of patients about their condition. Currently, the European Union’s priority is to improve the quality of life of patients suffering from chronic non-communicable diseases. The studies on the quality of life are an interdisciplinary area, combining the clinical significance and the psychological aspects of medical care.